Persistent hyponatremia in an elderly patient - Yin, Ye Lai; Samsudin, Intan Nureslyna; Mohamed Mokhtar, Normaizuwana; Thambiah, Subashini C. (American Association of Clinical Chemistry, 2020)
A 78-year-old male with early dementia and long-standing hypertension presented with acute, self-resolving left-sided body numbness. He was hypertensive (168/92 mmHg) but otherwise stable, euvolemic with no other clinical signs and symptoms. He was not on any other medications besides Telmisartan.